Smart Delivery Agent - Hazhari, Muhammad Haiqal; Azizi, Muhammad Arief; Zariman, Asnazulfadhli (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
This study develops a Smart Delivery Agent that made by using the Arduino. The smart car can be used to help worker in warehouse, especially on the busy season. By using the smart car, the unloading and movement of the item in postal warehouse or the company can be more organize and faster. The purpose of the project is to modernize Pos Laju work with more organize, fast and to achieve the same level with the other courier service on other countries. The limit of range to control the smart car using smartphone Bluetooth is for 10 metres. The user is able to use the auto mode and set up mode to let the smart car work without the users have to go to in the range to control the smart car. However, the smart car can only carry certain items on top of the car as long as the item is not over 400 grams. The design of the smart car can be redesign so that it can carry big item/parcel without any problem.